2019
DOI: 10.1103/physrevapplied.11.044058
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Investigation of Charge Trapping Across the Crystalline- Si –Amorphous- SiO2 Interface

Abstract: Accurate microscopic description of the charge trapping process from semiconductor to defects in dielectric oxide layer is of paramount importance to understanding many microelectronic devices like the complementary metal-oxide-semiconductor (CMOS) transistors, as well as electrochemical reactions. Unfortunately, most current microscopic descriptions of such processes are based on empirical models with parameters fitted to experimental device performance results or simplified approximations like the Wentzel-Kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…All calculations, including geometry optimization and electronic structure calculation, were performed with the Norm-Conserving Pseudopotential (NCPP) implemented in the plane-wave package PWmat code 27,28 which has been proven to be an accurate and efficient package to calculate large semiconducting systems. 29 The Perdew-Berk-Ernzerhof (PBE) exchange-correlation functional was used 30,31 to optimize the structure with a plane wave energy cutoff of 60 Ryd. The Monkhorst-Pack k-point mesh was set to 3 Â 2 Â 1 for the model of 98 atoms, and the force threshold was set to 0.02 eVÅ À1 .…”
Section: Methodsmentioning
confidence: 99%
“…All calculations, including geometry optimization and electronic structure calculation, were performed with the Norm-Conserving Pseudopotential (NCPP) implemented in the plane-wave package PWmat code 27,28 which has been proven to be an accurate and efficient package to calculate large semiconducting systems. 29 The Perdew-Berk-Ernzerhof (PBE) exchange-correlation functional was used 30,31 to optimize the structure with a plane wave energy cutoff of 60 Ryd. The Monkhorst-Pack k-point mesh was set to 3 Â 2 Â 1 for the model of 98 atoms, and the force threshold was set to 0.02 eVÅ À1 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the WKB approximation has only been used in single-interface systems such as Si/SiO2, and its validity in multiple-interface systems is quite questionable (as the wave function can be bounced by at the interface). Even in single-interface Si/SiO2 system, our previous work has shown that the WKB approximation can underestimate the coupling strength of two states [18].…”
Section: Density-functional Theory Simulationmentioning
confidence: 96%
“…As discussed in one of our previous studies on charge trapping across Si/SiO2 interfaces [18], the accurate atomistic simulation of the charge trapping process is possible only after a few technical challenges have been overcome. These include realistic interface structures, correct theoretical band alignment, and the application of adequate charge transfer theories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marcus theory is also often used to describe electron transitions from one state to another, especially for electronic states located at different positions 17 . While the energy barrier of the Marcus theory also comes from atomic displacements (hence the diagonal elements of electron-phonon coupling), the electronic coupling can come from different sources, e.g., an applied electric field, or more intrinsic coupling.…”
Section: ∂R ∂ϕ In (R) ∂Rmentioning
confidence: 99%